Sensor Relocation Technique Based Lightweight Integrated Protocol for WSN - J. Joy Winston; B. Balan Paramasivan (International Journal of Distributed Sensor Networks)
While deploying sensor nodes for sensitive services, we need to focus on both the coverage and connectivity. The sensor relocation scheme had been proposed earlier, where the sensors themselves move towards the required position to make proper coverage and connection. From our experimental results, we noted that this work achieves good coverage. However, this approach fails to focus on connectivity issue due to node migration and secured communication too, which may compromise our collecting data. To address these serious issues, we proposed an efficient sensor relocation technique based lightweight integrated protocol (LIP). We have implemented and studied thoroughly our proposed work. From our experimental results, our proposed work LIP outperforms the existing sensor relocation scheme in terms of network connectivity, coverage, throughput, packet delivery fairness, energy consumption, energy loss, network resiliency, and secured communication. It is also noted that our proposed model maximizes the lifetime of wireless sensor networks.